The impact of human leukocyte antigen mismatch on recipient outcomes in living‐donor liver transplantation. Issue 10 (4th July 2022) - Tajima, Tetsuya; Hata, Koichiro; Kusakabe, Jiro; Miyauchi, Hidetaka; Yurugi, Kimiko; Hishida, Rie; Ogawa, Eri; Okamoto, Tatsuya; Sonoda, Mari; Kageyama, Shoichi; Zhao, Xiangdong; Ito, Takashi; et al.
Abstract: Donor–recipient human leukocyte antigen (HLA) compatibility has not been considered to significantly affect liver transplantation (LT) outcomes; however, its significance in living‐donor LT (LDLT), which is mostly performed between blood relatives, remains unclear. This retrospective cohort study included 1954 LDLTs at our institution (1990–2020). The primary and secondary endpoints were recipient survival and the incidence of T cell–mediated rejection (TCMR) after LDLT, respectively, according to the number of HLA mismatches at all five loci: HLA‐A, HLA‐B, HLA‐C, HLA‐DR, and HLA‐DQ. Subgroup analyses were also performed in between‐siblings that characteristically have widely distributed 0–10 HLA mismatches. A total of 1304 cases of primary LDLTs were finally enrolled, including 631 adults (recipient age at LT ≥18 years) and 673 children (<18 years). In adult‐to‐adult LDLT, the more HLA mismatches at each locus, the significantly worse the recipient survival was ( p  = 0.03, 0.01, 0.03, 0.001, and <0.001 for HLA‐A, HLA‐B, HLA‐C, HLA‐DR, and HLA‐DQ, respectively). This trend was more pronounced when multiple loci were combined (all p  < 0.001 for A + B + DR, A + B + C, DR + DQ, and A + B + C + DR + DQ). Notably, a total of three or more HLA‐B + DR mismatches was an independent risk factor for both TCMR (hazard ratio [HR] 2.66, 95% confidence interval [CI] 1.21–5.87; p  = 0.02) and recipient survival (HR 2.44, 95% CI 1.11–5.35; p  = 0.03) in between‐siblings . By contrast, HLA mismatch did not affect pediatric LDLT outcomes at any locus or in any combinations; however, it should be noted that all donor–recipient relationships are parent‐to‐child that characteristically possesses one or less HLA mismatch at each locus and maximally five or less mismatches in total. In conclusion, HLA mismatch significantly affects not only TCMR development but also recipient survival in adult LDLT, but not in children.